Special Issue on Scheduling Theory and Algorithms for Sustainable Manufacturing - Alexandre Dolgui; David Lemoine; María I. Restrepo; Frank Werner (Algorithms)
The following Special Issue was initiated at the 10th IFAC triennial conference MIM 2022 (https://hub [...]